Integrated Recruitment of Remote Sensing and GIS Techniques for the Analysis of the Geomorphic Properties of the Kandaran Valley Basin in Sulaymaniyah - Abbas Yas, Nebras (Al-Adab Journal, 2019)
The objective of the study is to identify and analyze the characteristics of the morphometric and its impact on the formation of the geomorphic manifestations of the Kandaran Valley Basin in Sulaimaniyah Province, which consists of spatial (geometric), formalistic and topography characteristics as well as the drainage system, and to determine the effect of these characteristics in the nature of runoff, the relational relationship between the morphometric characteristics and the geological structure of the study area and the development of some morphometric characteristics, as well as the identification of the main river discharge patterns in the study area. The determination of the direction of runoff and watershed relies on remote sensing and the systems of Geographic information using the tool for morphometric measurements (HEC- RAS), topographic maps, and digital terrestrial elevation model (DEM) to prepare a river network map (mattresses and river basins) and based on the (Strahler) classification. Six river mattresses were identified, and three main basins; they are (Kandaran, Qaziawa, Kwandole), and the spatial data, images, satellite imagery and imagery of satellites and radar images for the year 2017 were analyzed and used in the applied study, and the contour height lines, the gradient (slope) and the downward trend were extracted ( Aspect) as well as determining the form of the slope through the (curvature) and using these characteristics to determine the direction of runoff and determine the best places for water rafting in the study area.